Pocket glossary for commonly used research terms - Holosko, Michael J. (Sage Publications, 2011)
This extensive glossary contains over 1500 research and statistical terms, written in jargon-free, easy-to-understand terminology to help students understand difficult concepts in their research courses. This pocket guide is in an ideal supplement to the many discipline-specific texts on research methods and statistics.